PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA STUDI PADA SMK NEGERI KABUPATEN PEMALANG - Marheni Setyowati, 12.5202.0142 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The success of teachers in performing their duties as well as an indicator of teacher performance can be known from studentâs learning achievement. The purpose of this study is to examine and analyze the effect of teachers discipline on job satisfaction in all Pemalang SMK, test and analyze the effect of motivation on job satisfaction of teachers in all Pemalang SMK, test and analyze the effect of teacher discipline on the performance in all Pemalang SMK, test and analyze the effect of motivation on teacher performance in all Pemalang SMK The method used in this research is descriptive method with a quantitative approach. The population of this study was all Pemalang SMK teachers as many as 314 people. The sample was 176 people that were taken proportionally in each school. To determine the effect of independent variables on the dependent variable multiple linear regression analysis were used. Based on the analysis of data it can be concluded that the discipline has positive and significant effect on job satisfaction of teachers in all Pemalang SMK. Motivation has positive and significant effect on job satisfaction of teachers in all Pemalang SMK. Discipline positive and significant impact on teacher performance in all Pemalang SMK. Motivation has positive and significant impact on teacher in all Pemalang SMK. Satisfaction has positive and a significant effect on teacher performance in all Pemalang SMK. Job satisfaction does not mediate the effect on performance of work discipline. Job satisfaction mediates the effect of job motivation on performance Keywords: Work Discipline, Work Motivation, Job Satisfaction, Teacher Performance